2014
DOI: 10.1002/apj.1794
|View full text |Cite
|
Sign up to set email alerts
|

Study on the process of fermentation coupling with foam fractionation and membrane module for nisin production

Abstract: Nisin, an antimicrobial peptide, is commercially used as a food preservative and a promising alternative in medical applications for inhibiting bacterial infection in both humans and livestock. It is produced by fermentation using certain strains of Lactococcus lactis ssp. lactis. In traditional fermentation, the yield of nisin has always been limited by adsorption of nisin onto its producer, enzymatic degradation and product inhibition. This limitation can be solved by fast removal of the product from the bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…During the process of foam fractionation, the high SDS concentration in the leaching solution would result in the low foam drainage because of high viscosity and bad fluidity. Currently, changing column shape, increasing temperature and adding internal component were usually used for promoting foam drainage by increasing the fluidity of the loading solution . In this work, a column with a spherical part was used as the experimental column, and a cylindrical column was used as a control column.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the process of foam fractionation, the high SDS concentration in the leaching solution would result in the low foam drainage because of high viscosity and bad fluidity. Currently, changing column shape, increasing temperature and adding internal component were usually used for promoting foam drainage by increasing the fluidity of the loading solution . In this work, a column with a spherical part was used as the experimental column, and a cylindrical column was used as a control column.…”
Section: Resultsmentioning
confidence: 99%
“…Foam fractionation is a bubble adsorptive separation technology, and it has been widely used to separate a trace material with surface activity from its aqueous solution . Currently, foam fractionation has also aroused the interest of bioengineering researchers because of simple equipment, low cost and environmental compatibility . In this case, foam fractionation is continually developed to recover a non‐surface‐active material from the industrial effluents based on its specific interactions with a surfactant which is used as the collector .…”
Section: Introductionmentioning
confidence: 99%
“…The loss of cells in FCFS was less than that in foam separation of part 1 because growth of cells offset the loss to some extent. The increase of polymyxin E was because on the one hand foam separation relieved the product inhibition; [13,33] on the other hand, the air inlet met the need of oxygen in aerobic fermentation. It cannot be ignored that FCFS technology not only increased polymyxin E total titer but also obtained two kinds of liquid-foamate and residual broth.…”
Section: Fermentation Coupling With Foam Separationmentioning
confidence: 99%
“…Heyd et al [3] reported that bacteria could be entrapped in magnetic alginate beads to prevent loss of the cell through foaming. Cui et al [13] developed a technology of fermentation coupling with foam fractionation and membrane module. However, previous studies were difficult to scale up because of complexity or being restricted to anaerobic fermentation (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation